Nodal signalling in Xenopus: the role of Xnr5 in left/right asymmetry and heart development. Issue 8 (August 2016) - Tadjuidje, Emmanuel; Kofron, Matthew; Mir, Adnan; Wylie, Christopher; Heasman, Janet; Cha, Sang-Wook
Abstract : Nodal class TGF-β signalling molecules play essential roles in establishing the vertebrate body plan. In all vertebrates, nodal family members have specific waves of expression required for tissue specification and axis formation. In Xenopus laevis, six nodal genes are expressed before gastrulation, raising the question of whether they have specific roles or act redundantly with each other. Here, we examine the role of Xnr5. We find it acts at the late blastula stage as a mesoderm inducer and repressor of ectodermal gene expression, a role it shares with Vg1. However, unlike Vg1, Xnr5 depletion reduces the expression of the nodal family member xnr1 at the gastrula stage. It is also required for left/right laterality by controlling the expression of the laterality genes xnr1, antivin ( lefty ) and pitx2 at the tailbud stage. In Xnr5-depleted embryos, the heart field is established normally, but symmetrical reduction in Xnr5 levels causes a severely stunted midline heart, first evidenced by a reduction in cardiac troponin mRNA levels, while left-sided reduction leads to randomization of the left/right axis. This work identifies Xnr5 as the earliest step in the signalling pathway establishing normal heart laterality in Xenopus .